The untold war at sea : America's revolutionary privateers - Hulbert, Kylie A., 1984- (The University of Georgia Press, 2022)
"Sailing in the waters of the Atlantic and the Caribbean throughout the eighteenth-century, privateers played a vital role in numerous European and Anglo-American conflicts. This book extends that story to the role of privateers in the American Revolution. Privateer operations provide a fresh perspective on the impact and influence of the Revolution as a global conflict. Revolution-era engagements are not only between British Regulars, German mercenaries, and colonial patriots, but also privateers, include international crews operating in international waters on an international stage. These merchant marines understood that the war not only consisted of battlefields on American soil but required foreign support and aid. International recognition was imperative. The process of revolution and winning independence was global in nature and privateers operated at its core. Their experiences, rather than being unfamiliar and unknown, are an integral part of the story which this book highlights, reintegrating their story into the popular, patriotic narrative"--